Implementación de un banco de sensores aplicados a sistemas de seguridad de uso residencial. - Ludeña Suárez, Marco Alejandro (2012)
This research work aims to the implementation of a bank of sensors applied to security systems for residential use, in order to inform students of the Department of Energy, Industry and nonrenewable natural resources, with the adequate knowledge related to sensors in residential security systems. The subsequent chapters will provide detailed information about the elements used in this research work, and also a practical manual for the docents so they can provide the necessary skills and knowledge and the students could better understand and comprehend the importance that these elements as part of a security system. The use of these devices were tested and practiced in the manual, so that students will not have problems connecting or programming each sensor used in this research work. Finally in the last chapter sets out the conclusions and recommendations obtained during the development of this work